Passivity-based coordinated control for islanded AC microgrid. (1st November 2018) - Gui, Yonghao; Wei, Baoze; Li, Mingshen; Guerrero, Josep M.; Vasquez, Juan C.
Highlights: A passivity-based coordinated control for guaranteeing stability in islanded microgrid is proposed. It renders a phase-locked-loop-free synchronization for renewable energy source in the microgrid. It offers an enhanced plug-and-play capability of the renewable energy source in the microgrid. Stability is guaranteed regardless from the number of renewable energy source. Abstract: A novel passivity-based coordinated control strategy is proposed for an islanded AC microgrid including renewable energy source and energy storage system units. The main advantage is that the proposed coordinated control strategy manages the microgrid without using a phase-locked loop system. In the microgrid, the energy storage system supports the voltage of the microgrid, and the renewable energy sources inject their maximum power to the microgrid in the normal operation. For the energy storage system, we use a proportional-resonant controller, and for the renewable energy sources, we use a voltage modulated direct power control method, which has not only a good tracking performance but also a good steady-state behavior. Another advantage of the proposed method is that the asymptotical stability of the whole microgrid can be guaranteed by using the passivity principle when the heterogeneous renewable energy sources are integrated into the microgrid. To validate the proposed coordinated control law, we use a microgrid consisting of one energy storage system, one wind turbine, one photovoltaic and two controllable loads. Simulation results show that the plug-and-play capability of the wind turbine and photovoltaic in the microgrid is enhanced when comparing with the conventional vector current control method with a phase-locked loop system. Moreover, the voltage and frequency of the microgrid are recovered to its nominal value by the energy storage system with the proposed method as well. Finally, experimental verification of the proposed coordinated control algorithm is performed on a 10 kW microgrid system. The experimental results match the simulation ones as well.